Analysis of total leakage of finger seal with side leakage flow. (October 2020) - Zhao, Hailin; Su, Hua; Chen, Guoding
Abstract: The flow through the finger interstices and the micro voids in rough contact interface between finger sticks is considered as the side leakage flow of finger seal. The porous approach that the side leakage flow of finger seal is transformed into the seepage flow through a porous medium was proposed. The CFD model of total leakage of finger seal was established. When the side leakage flow is considered, the relative increment of total leakage of finger seal ranges from 3 to 6% in most cases. The work also shows that the total leakage without side leakage flow is between the leakage flowing into the main leakage clearance and the leakage exiting from the main leakage clearance when considering the side leakage flow. Highlights: The porous approach is used to study the side leakage flow of finger seal. The calculation method of resistance coefficients of porous medium for side leakage flow of finger seal is proposed. The influence of the surface morphology of finger element on the leakage of finger seal is analyzed quantitatively.